2017
DOI: 10.1155/2017/1462064
|View full text |Cite
|
Sign up to set email alerts
|

Parental Diabetes Behaviors and Distress Are Related to Glycemic Control in Youth with Type 1 Diabetes: Longitudinal Data from the DINO Study

Abstract: Objective To evaluate (1) the longitudinal relationship between parental well-being and glycemic control in youth with type 1 diabetes and (2) if youth's problem behavior, diabetes parenting behavior, and parental diabetes-distress influence this relationship. Research Design and Methods Parents of youth 8–15 yrs (at baseline) (N = 174) participating in the DINO study completed questionnaires at three time waves (1 yr interval). Using generalized estimating equations, the relationship between parental well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 34 publications
0
44
2
Order By: Relevance
“…Others have found that family cohesion is associated with healthy weight control practices within the T1D population . Eilander et al found that parental distress around diabetes care was associated with higher HbA1c levels. The questions selected to assess for conflict in our study were a small subset of questions taken from the Family and Diabetes Conflict Scale and therefore have not been validated and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Others have found that family cohesion is associated with healthy weight control practices within the T1D population . Eilander et al found that parental distress around diabetes care was associated with higher HbA1c levels. The questions selected to assess for conflict in our study were a small subset of questions taken from the Family and Diabetes Conflict Scale and therefore have not been validated and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…DEPS scores of 8 [4-11.7], 16 [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and 28 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], respectively, as shown in Figure 2.…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding parenting style, parents' use of authoritarian-like strategies was associated with poorer glycaemic control after 3 months (b = 0.189, P ≤ 0.05) and after 6 months (b = 0.254, P ≤ 0.05) of observation of children with new-onset diabetes (diabetes duration of <1 year at baseline) [7]. Eilander et al also reported an association between unsupportive diabetes-specific parenting behaviour (b = 0.383, P = 0.02) and parental diabetes distress (b = 0.276, P = 0.001), with poorer glycaemic control in children/ adolescents aged 8-15 years at baseline [8]. In addition, adolescents' perception of parental over-involvement in diabetes care (assessed by the parental involvement scale from the Diabetes Quality of Life for Youth -Short Form, score 0-12 [9]) was related to poorer metabolic control (b = 0.099, P < 0.001) and more episodes of diabetic ketoacidosis (b = 0.05, P < 0.001).…”
Section: Discussionmentioning
confidence: 95%